Moloka'i - Brennert, Alan (Moloka'i, 2004)
Dreaming of far-off lands away from her loving 1890s Honolulu home, seven-year-old Rachel is forcibly removed from her family when she contracts leprosy and is placed in a settlement, where she loses a series of new friends before new medical discoveries enable her reentry into the world.